School education on traffic safety values Interline - OUBBICHE, Samir (Social Sciences Journal, 2021)
This study aims to clarify the role that the school institution or the school upbringing in general can play in the prevention of one of the most social phenomena that have haunted humane societies in recent years, which is the phenomenon of traffic accidents and their devastating effects and repercussions on the individual, society and the state in various economic, social and health fields And others, and Algeria today is one of the most prominent of these countries that are witnessing the exacerbation of the phenomenon We have demonstrated through this consecutive study how the school, through its various classroom and extra-curricular activities and programs, can work on building traffic awareness among its members and gain them sound values in dealing with this phenomenon.